2017
DOI: 10.18632/oncotarget.15285
|View full text |Cite
|
Sign up to set email alerts
|

Age-adjusted charlson comorbidity index score as predictor of prolonged postoperative ileus in patients with colorectal cancer who underwent surgical resection

Abstract: Comorbidities had considerable effects on the development of postoperative ileus (POI). The primary aim of the present study was to determine the influence of the age-adjusted Charlson comorbidity index (ACCI) score on the risk of prolonged POI in patients with colorectal cancer who underwent surgical resection. Using the electronic Hospitalization Summary Reports, we identified 11,397 patients with colorectal cancer who underwent surgical resection from 2013 through 2015. Logistic regression models were appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 40 publications
2
24
0
Order By: Relevance
“…In addition, each diagnosis of disease and procedure in this study was made by ICD codes, which may cause bias from coding errors. However, the validity and reliability of this database have been proved in prior studies 32 , 33 . To minimize such potential confounding bias, we used the corresponding Chinese terms to check the identified diseases and procedures.…”
Section: Discussionmentioning
confidence: 92%
“…In addition, each diagnosis of disease and procedure in this study was made by ICD codes, which may cause bias from coding errors. However, the validity and reliability of this database have been proved in prior studies 32 , 33 . To minimize such potential confounding bias, we used the corresponding Chinese terms to check the identified diseases and procedures.…”
Section: Discussionmentioning
confidence: 92%
“…Patient demographics (age, gender, race, and insurance status) and hospital characteristics (rural, urban nonteaching, urban teaching, small bed size vs. large bed size, medium bed size vs. large bed size) were used as variables in predictive models. Charlson Comorbidity Index (CCI), [26][27][28][29] a validated predictor of inpatient mortality, hospital length of stay (LOS), 10-year mortality, and readmission, was used to assess patient preoperative health status. [30][31][32] Risk Factors and Adverse Events…”
Section: Independent Variablesmentioning
confidence: 99%
“…In addition, a recent retrospective study involving 11,397 patients who underwent open or laparoscopic colectomy showed that the high age-adjusted Charlson comorbidity index score was an independent predictor of POI prolongation [19]. Long operating time was a risk factor for POI in colorectal surgery [20].…”
Section: Discussionmentioning
confidence: 99%